Epidemiology of eye diseases: outcomes from a free provincial eye clinic in Papua New Guinea - Owusu-Afriyie, Bismark; Gende, Theresa; Silki, Frederick; Ishmael, Bolgii; Kuiaha, Joelda (Frontiers in Medicine, 2023)
Aim: To ascertain the prevalence and pattern of eye problems in Madang Province, Papua New Guinea. A six-month retrospective study was performed at Madang Provincial Hospital Eye Clinic. Convenience sampling was used in this study and all patient records from January to June 2020 were included. Data was extracted using Microsoft Excel and the data included gender, age, occupation, district where the patient lived, presenting visual acuity, and diagnosis. It was then analyzed using International Business Machines Corporation's Statistical Package for the Social Sciences version 26. A P-value of ≤ 0.05 was considered statistically significant. Results: A total of 1,715 patients received services at the eye clinic between January and June 2020, and 1,664 were included in this study. The mean age of the patients was 39.3 ± 20.3 years. There were slightly more males (50.4%) than females. The overall leading ocular morbidities were corneal ulcers and keratitis (20.7%), refractive errors (17.4%), and cataracts (16.8%). More than half of the patients (56.2%) were either visually impaired or blind. Nearly half of the patients (41.8%) traveled long distances to seek services at the eye clinic. There was a significant association between demographic characteristics, diagnosis, and level of visual impairment. There is a high prevalence of potential causes of visual impairment and blindness in Madang Province and these conditions affect all age groups and genders. It is essential to increase accessibility to eye care services in the country.